Stabilization and financial adjustment in the Caribbean : a thirty-year perspective - Jones-Hendrickson, Simon ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1998)
Discusses and evaluates the twin issues of stabilization and financial adjustment in a set-theoretic framework. Focuses on the critical moments of policy adjustments in the Caribbean, given the present era of internationalization, liberalization and globalization.